Voltage-Controllable Guided Propagation in Nematic Liquid Crystals - Hsin-Yu Yao; Shang-Min Yeh (Advances in Condensed Matter Physics)
Voltage-controllable guided channels are formed in a planar nematic liquid crystals cell. The director of liquid crystals can be aligned by applying external voltage, which results in a difference of the refractive index between two adjacent channels; therefore, the incidence beam can be coupled from one channel to another. First, we discussed the propagation of the beam and the self-focusing in a single channel; then we discussed the propagation of the beam and the coupling effect in the two channels. The results showed that the propagation of the beam can be selected in each channel by applying voltages in the two individual electrode channels.